Religious Pluralism in the Framework of Pancasila Ideology - Mirwan Fikri Muhkam; Sukri Badaruddin (Fakultas Syariah dan Hukum Islam Institut Agama Islam Negeri Bone, 2021)
This study aims to explore the value of Pluralism to strengthen the unity of the nation's diversity. Ignorance of cultural values originating from the values of Pancasila is a mistake as a citizen who believes in God because Pancasila is in line with religious values. Pluralism is not just about diversity, but the involvement of diversity itself.Awareness of this plurality will lead to an attitude of mutual understanding of beliefs between citizens and in turn morality will be realized. This research method is qualitative in nature which examines various writings, both books and journals related to Pancasila education, pluralism, multicultural education, and the diversity of Indonesian society.The results of this study found that (1) in a democratic country such as Indonesia, which has the uniqueness of Pancasila democracy, pluralism must be a strength, because without pluralism, the concept of democracy will not be established in Indonesia, (2) through inter-religious education based on culture can prevent penetration outside culture (westernization) and wise use of technology can prevent potential divisions, and (3) Pancasila is a reference to reduce excessive fanaticism and encourage religious activities with respect for other religious people.The implication of this study is that diversity in Indonesia is unique and must be accepted by citizens by respecting each other between religious communities.